Between Reforms and Uncertainty. Public Economy and Civil Rights in Valentín de Foronda - Wilianny I. Calatayud Torre Alba; Laura J. López Medina; Giovanni Patriarca (Estudios de Historia de España, 2019)
In a comparative analysis, the political philosophy and the economic thought of Valentín de Foronda are presented. In his works, the modern social ideas merge with the theories of criminal law in a detailed study of the impediments of development. His pedagogical approach has been the driving force for a series of reflections – both pragmatic and metapolitical – about the structure of the state and the nature of justice.